Analisis Percepatan Pelaksanaan Pekerjaan pada Pembangunan Gedung Laboratorium Medis Poltekkes Surabaya Menggunakan Metode Crashing - Pratiwi, Ari Rahma; Sarya, Gede (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This research investigates problems in projects that have been carried out by CV. MKE, such as late work occurring in the eighth week of progress. Where in the eighth week there was a deviation of -2.618%. So an analysis of the acceleration of work is needed. In this research, the analysis was carried out using the Crashing method by adding working hours (overtime) with the help of Microsoft Project 2016 software to find the critical path. After getting the critical path results, an analysis of time and costs will then be carried out. Based on the results of the analysis of time and cost calculations using the Crashing method, it shows that with the additional working hours, the project duration can be reduced by 11 days from the normal duration of 140 days, so that the total work duration becomes 129 days and achieves an efficiency of 7.857%. Then there was a change in the total project cost of Rp. 11,547,870,543.73 from the normal fee of Rp. 11,575,779,000.00 with a cost difference of Rp. 27,908,456.27 and get an efficiency of 0.241%.